State and Aims of Enhancement of Health and Social Care for Child Population - Alexander A. Baranov; Valery Yu. Albitskiy; Nataliya V. Ustinova ("Paediatrician" Publishers LLC, 2020)
The article discusses the major steps in development of health and social care for the child population in Russian Federation. Principal legislative and regulatory acts covering the medical care provision are specified. Two regional organizational models of health and social care for the child population were presented, they have shown their effectiveness. Principle problems for the development of systematic approach to the organization of health and social care for children in Russia are listed. Moreover, main directions for its development and nearest prospects associated with the implementation of program activities carried out within the framework of the Decade of Childhood.